Easter horseback processions in Upper Lusatia - from ‘waking’ nature to the religious and national idea - Nowak, Tomasz (Interdisciplinary Studies in Musicology, 2018)
Horseback processions are an historical phenomenon still alive today in many parts of Europe. In western Slavic lands (Poland, Czech Republic, Lusatia) they are all inseparably connected with the period of Easter, and one of the crucial elements of the processions is song. Behaviour observed in Slavic horseback processions can be directly related to the establishing of the world by delimiting boundaries and ordering and sacralising space. Taking place as they do in specific conditions undoubtedly exemplify a rite of passage. In this rite, the costume and pious symbols serve to take the participants away from the world of the profane and bring them to the realm of the sacred, while the ‘carrying on horseback’, besides its utilitarian use during chases, serves to maintain them in an ‘intermediate state, between earth and heaven’, for them to ‘transcend themselves’ and undertake a ‘mystical journey’. Processions cultivated among the Upper Lusatians and the available sources allow one to draw conclusions regarding not only the function of song and of the tradition itself, but also the way they have changed down the ages. Interesting to the musicologist is the change in the functions of the processional singing from a signal directed at nature, through a documented religious medium, to the symbolisation of social (national) meanings, making use of contemporary media. As such, these functions may serve indirectly the interpretation of such complex and poorly documented customs as Silesian processions, and especially the special social role of the processional spiewak (cantor).